2020
DOI: 10.1136/lupus-2020-000388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of progressive multifocal leukoencephalopathy (PML) in adults and children with systemic lupus erythematosus

Abstract: ObjectiveTo define the risk of progressive multifocal leukoencephalopathy (PML) in SLE.MethodsThis is a retrospective observational study to evaluate PML cases in patients with SLE admitted to two large academic hospitals. Using electronic medical record (EMR) data, International Classification of Diseases (ICD) codes identified PML cases among patients with SLE, rheumatoid arthritis (RA) (controls), had renal transplant and with HIV. Medication exposure was reviewed.ResultsA total of 5409 Columbia University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Children with SLE, as compared to adult patients, may have a lesser risk for PML despite being immunocompromised from medications or active SLE. It has been observed that PML associated with autoimmune disorders had a more favorable prognosis when compared with PML caused by other disorders such as HIV or malignancy 9…”
Section: Discussionmentioning
confidence: 99%
“…Children with SLE, as compared to adult patients, may have a lesser risk for PML despite being immunocompromised from medications or active SLE. It has been observed that PML associated with autoimmune disorders had a more favorable prognosis when compared with PML caused by other disorders such as HIV or malignancy 9…”
Section: Discussionmentioning
confidence: 99%
“…No cases of progressive multifocal leukoencephalopathy (PML) due to John Cunningham virus, which is mostly seen with natalizumab treatment, 89,90 have been recorded in MS patients treated with rituximab, and the frequency of PML in non-neurologic patients treated with rituximab seems to range around 1:4000; however, usually these patients have received multiple immunosuppressants. 91,92 Finally, an added advantage of rituximab is its relatively low cost (biosimilars are also available); however, its off-label prescription is complex and time-consuming for physicians. While open questions remain about optimal dosing and frequency strategies, a common tactic is 2 × 500 or 1000 mg, in a 14-day period, and repeat dosing of 500–1000 mg every 6 months or yearly.…”
Section: Anti-b-cell Agents As a Therapeutic Strategymentioning
confidence: 99%
“…Reports of PML cases in patients treated with Rituximab have raised concerns about its use in renal transplant recipients, since the risk seems to be higher in patients treated with multiple immunosuppressive drugs [28]. However, the incidence of this potentially fatal complication seems to be very low both in patients with autoimmune disorders and in renal transplant recipients [29,30]. Alemtuzumab is a humanized anti-CD52 monoclonal antibody that is used as induction or anti-rejection therapy in renal transplant recipients.…”
Section: Other Immunosuppressive Agentsmentioning
confidence: 99%